2013
DOI: 10.1097/mao.0b013e318277a282
|View full text |Cite
|
Sign up to set email alerts
|

Bone-Anchored Hearing Implant Loading at 3 Weeks

Abstract: The current study suggests that loading the implant and 6-mm abutment with the sound processor at 3 weeks is safe. The stability of the implant as measured by ISQ values had reached its baseline value within 3 weeks after implantation. The degree of stability was not affected by implant loading. Only mild skin reactions were observed incidentally. This study supports the use of early loading at 3 weeks as current practice in healthy adults with good bone quality; thus, these adults can benefit from the rehabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 28 publications
6
23
1
Order By: Relevance
“…The six-month report showed higher mean Implant Stability Quotient (ISQ) values and less soft tissue reactions for the new, wider implant compared to the previous generation implant. The good outcomes could be confirmed in other studies [3][4][5] and in long term follow up [6], and resulted in a complete substitution of the previous generation implant in all new BAHI surgeries, not only in adult patients but also in the pediatric population. During the last few years, however, in both centers, we noticed a high incidence of soft tissue reactions, revision surgery and non-users in our pediatric BAHI population.…”
Section: Introductionsupporting
confidence: 52%
“…The six-month report showed higher mean Implant Stability Quotient (ISQ) values and less soft tissue reactions for the new, wider implant compared to the previous generation implant. The good outcomes could be confirmed in other studies [3][4][5] and in long term follow up [6], and resulted in a complete substitution of the previous generation implant in all new BAHI surgeries, not only in adult patients but also in the pediatric population. During the last few years, however, in both centers, we noticed a high incidence of soft tissue reactions, revision surgery and non-users in our pediatric BAHI population.…”
Section: Introductionsupporting
confidence: 52%
“…Given the high initial stability, and the fact that ISQ values are increased already at 10 days after implantation, earlier loading seems feasible, at least for patients with normal bone quality. Indeed, successful loading of wide diameter implants 3 to 4 weeks after surgery has recently been reported (18,20). There is some stability variance between the patients; this variance is mainly caused because of abutment length 9 mm on 3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 62 participants will be recruited at the ear, nose and throat outpatient departments by the (local) researchers. Patients are considered eligible for participation [22, 39] (I) if they will undergo unilateral BCHI surgery and (II) when they are ≥ 18 years of age. Participants will be excluded from participation in case of (I) a history of immunosuppressive disease, (II) usage of systemic immunosuppressive medication, (III) bilateral BCHI placement, (IV) relevant dermatological disease (e.g., psoriasis, severe eczema), (V) participation in other studies, and (VI) when no suitable site for a 4-mm-wide implantation during surgery is found.…”
Section: Methodsmentioning
confidence: 99%